Comparative And Functional Genomics Of Actinobacteria And Archaea - Gao, Beile (My University, 2009)
The higher taxonomic groups within Prokaryotes are presently distinguished mainly on the basis of their branching in phylogenetic trees. In most cases, no molecular, biochemical or physiological characteristics are known that are uniquely shared by species from these groups. Comparative genomic analyses are leading to discovery of molecular characteristics that are specific for different groups of Bacteria and Archaea. These markers include conserved inserts and deletions in universal proteins and lineagespecific proteins, which provide novel means for identifying and circumscribing these groups of prokaryotes in clear molecular terms and for understanding their evolution. Because of their taxa specificities, further studies on these newly discovered molecular characteristics should lead to discovery of novel biochemical and physiological characteristics that are unique to different groups of microbes. The focus of my project was phylogenomic studies for two large prokaryotic group: Actinobacteria and Archaea. My goals were to a) identify molecular markers that are specific to Actinobacteria and Archaea at different taxonomic levels, which will help to understand the phylogenetic relationship within these two major groups; b) understand the functional significance of Actinobacteria-specific proteins. By comparative genomics approach, a number of conserved indels in various proteins (viz. Coxl, GluRS, CTPsyn, Gft, GlyRS, TrmD, Gyrase A, SahH and SHMT) have been identified that are specific for all Actinobacteria and additional indels were found to be unique to its major subgroups, such as Corynebacterineae, Bifidobacteriaceae, etc. In parallel, a large number of proteins were discovered to be restricted to Actinobacteria at different phylogenetic depths. These identified conserved indels and proteins for the first time provide useful markers for defining and circumscribing the Actinobacteria phylum or its subgroups in clear molecular terms. Similar comparative genomic studies have been carried out on Archaea and a vast number of proteins have been identified that are unique to Archaea or its various lineages. Lastly, I have performed functional studies on one of the Actinobacteria-specific proteins (ASPl). The structure of ASPl was determined and structural comparison indicates that the function of this protein might be novel since it does not match any known protein with or without known function.
Keywords: Prokaryotes; phylogenetic trees; Actinobacteria; Archaea; phylogenetic; phylum